Chapter 6 International financial system versus economic stability - Komorowski, Jan; Komorowski, Piotr (Taylor & Francis, 2024)
The struggle for world leadership between China and the United States, resulting in Russia's war with Ukraine, among other things, underscores the reality of structural changes in the global economy and the global system. This book explains that a new era of egocentrism and polycrisis in a multipolar system has emerged in international economic policy, with a strong drive toward interventionism and protectionism of national economies. Dynamic economic imbalances are becoming a constant factor in disrupting international competitiveness and forcing changes in both monetary policy and general economic policy. This prompts a new, more pragmatic definition of fundamental concepts in the theoretical sphere as well as an up-to-date and viable cause-and-effect narrative that is not disconnected from decision-making processes in the economic and political spheres. This book provides a comprehensive diagnosis of the current global economy landscape and evaluates the processes affecting the economic and financial realities and the effectiveness of economic policies. The recent dynamics have rendered much of the existing literature outdated or confined to individual economies, economic systems, and regions. The book describes the evolution of international economic policy, offering a comparative analysis of foreign trade theories, especially in the context of macroeconomic trends and the impact of international trade in goods and services in the new balance of power of the global economy. Targeted primarily at academics, students, and researchers in economics, finance, international relations, and management, it will also serve as a valuable resource for policymakers shaping and implementing contemporary state economic policies.